THE STANDING OF GUARANTEE AND FIDUCIARY AGREEMENTS ON THE MUDHARABAH CONTRACTS IN THE SHARIA BANKING - Pane, Sanusi Gazali; Sudiarti, Sri (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2021)
As a sharia-based banking product, the debate about the existence of mudharabah contracts and other products is always interesting to study as an effort to purify the understanding of fiqh and adapt to changing times. The basic principle of the mudharabah contract does not require collateral stipulation because this contract is different from qard and Rahn. Other than the unknown in classical and contemporary literature, guaranty provision even leads to restrictions on the relationship between sharia economics and community economic development. In practice, the mudharabah contract is followed by a fiduciary and mortgage, namely a contract that grants execution rights to banks. The fiduciary agreement is a loan-borrowing contract but applied to the mudharabah contract as an additional agreement outside the main deal. If the bank executes the mortgage, the mudharib will suffer two losses, namely the cost of capital and loss of assets due to the transfer of property rights. However, banks can set a fair policy for customers who want a contract without collateral on the one side but avoid the risk of moral hazard on the other side. 1) by conducting an investigative audit of the company to obtain asymmetric information about the company's ability to carry out the project. Likewise, the effect of information on potential business risks, financial capabilities, and the rigidity of the payment system of the company's business partners on the continuity of the contract. 2. Posit a financing account in a particular account, not a company account as usual, useful in monitoring and controlling financing. 3. Assign a special officer similar to an account officer to oversee contract agreements and contact business partners about the company's performance to analyze business continuity and minimize risks..